Genetic diversity within Leiurus quinquestriatus (Scorpiones: Buthidae) populations in Egypt as inferred from 16S mDNA sequence analysis. Issue 3 (2nd July 2020) - Sarhan, Moustafa; Badry, Ahmed; Younes, Mahmoud; Saleh, Mostafa
Abstract : The highly toxic and medically important scorpion Leiurus quinquestriatus is the most common scorpion species in Egypt and in some regions, is medically problematic for the local population. We studied variation in the mitochondrial 16S rRNA gene within 12 populations from different ecogeographical regions of Egypt. Our results indicate a high genetic variation among L. quinquestriatus populations with five haplotypes existing. Our data also suggests the existence of a distinct population of L. quinquestriatus in Sinai which may be a separate species.